2020
DOI: 10.1080/19475683.2020.1714727
|View full text |Cite
|
Sign up to set email alerts
|

Geographic proximity, trade and economic growth: a spatial econometrics approach

Abstract: This paper examines economic growth in terms of 'bilateral trade flow' and 'geographical distance' using the spatial dynamic panel data model for the period 1992-2016. The findings illustrate that the effect of spatial spillover or spatial dependence is one of the main economic growth determinants. Also, we find out that spatial relationships across countries and the spatial effects of trade are quite relevant. A country's economic growth is actually affected by the performance of its neighbours and trade part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 35 publications
1
30
0
1
Order By: Relevance
“…(3), economic growth is represented by y where N × 1 vector of dependent variable observations are collected at n points in space, X is N × K matrix of explanatory variables and ε i N × 1 is vector of normal errors which has constant variance. Given W ij represents N × N diagonal matrix containing distance-based weights (1)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(3), economic growth is represented by y where N × 1 vector of dependent variable observations are collected at n points in space, X is N × K matrix of explanatory variables and ε i N × 1 is vector of normal errors which has constant variance. Given W ij represents N × N diagonal matrix containing distance-based weights (1)…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, their results indicated that taxation has heterogeneous effects on income as a result of the type and sign of the tax coefficients b heterogeneous for the country-specific results. Amidi and Fagheh Majidi [1] investigated the geographical proximity, trade and economic growth with a spatial econometrics approach for EU countries over the period 1992-2016. They recognized that spatial relationships across countries and the spatial effects of trade are quite relevant.…”
Section: Review Of Literature and Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 On the importance of geographical proximity in the channels of propagation of crises, see, for example: De Gregorio and Valdes ( 2001 ), who argue that proximity of countries or regional effects are more important than trade links and/or macroeconomic similarities (ibid., p. 311), Glick and Rose ( 1999 ), ‏Amidi and Majidi ( 2020 ), Tobler ( 1979 ), and Sabkha et al ( 2019 ). …”
mentioning
confidence: 99%
“…Ayrıca AB ülke grubunun birbiri ile olan ticari ilişkisi ve bağlantısı düşünüldüğünde araştırmaya değer bir dinamiği bulunmaktadır. Çünkü kimi çalışmalar da bu husus coğrafi yakınlık ya da ikili ticaret akışı bağlamında ele alınmıştır (Amidi & Majidi, 2020). Bu çalışmanın evrenini oluşturan AB ülkelerinde İngiltere'nin de gruptan çıkmasından dolayı AB-28 yerine AB-27 ele alınmıştır.…”
unclassified